Degenerative Myelopathy in Brazilian Golden Retriever: Evaluation of the Association with Allele Frequency of the SOD1:c.118G>A Variant - Issamu Urushibata Ito, Fabio; Garrido Albertino, Lukas; Michelsen de Andrade, Fabiana; Secorun Borges, Alexandre; Oliveira-Filho, José Paes (Acta Scientiae Veterinariae, 2024)
Background: Canine degenerative myelopathy represents a progressive neurodegenerative disorder impacting the spinal cord. Initial clinical signs of canine degenerative myelopathy are typically observed in animals around 8 years of age. The clinical signs are characterized by general proprioceptive ataxia and spastic paresis of the pelvic limbs, with an irrepressible progression to flaccid paraplegia after 1 year of the appearance of the signs. Therefore, canine degenerative myelopathy is considered a differential diagnosis for medullary neoplasms, disc protrusion, and hip dysplasia, and since the clinical signs presented by the animals are similar in all these diseases, genetic testing plays an important role in diagnosis. In several dog breeds degenerative myelopathy was linked to the c.118G>A autosomal recessive variant in exon 2 of the superoxide dismutase 1 (SOD1) gene (SOD1:c.118G>A). In addition, the SOD1:c.118G>A variant in more than 124 breed dogs, suggesting that this variant is widely spread and fixed in the species before the breeds’ origin. However, there are few studies evaluating this variant in brazilian dogs, and none of them have evaluated it in the Brazilian Golden Retriever dogs. Therefore, this study aimed to evaluate the allele frequency of the SOD1:c.118G>A variant in Golden Retriever dogs from Brazilian kennels. Materials, Methods & Results: A total of 122 Brazilian Golden Retriever DNA samples were used in a PCR procedures with specific primers, previously described, to amplify a 779 base pairs amplicon containing the SOD1:c.118G>A variant in this study. a non-template control reaction was performed to check possible contamination in the PCR preparation. The genotyping of the animals was performed by direct Sanger sequencing of PCR products that amplified a fragment containing the variant. Considering the 95% confidence interval, the sample size used in the present study was slightly larger than the minimum required to assess the allele frequency of SOD1:c.118G>A variant (122 versus 113 samples). All animals assessed in this study were clinically normal at the time of sampling and were identified as wild-type for the SOD1:c.118G>A variant. Therefore, no alleles of the pathogenic variant (A) were found in the studied population. Discussion: Although all animals assessed in this study were classified as wild-type, this study is the 1st report in Brazil to evaluate the prevalence of this variant in Golden Retriever dogs. The poor prognosis and inexorable progression of canine degenerative myelopathy force most owners to opt for early euthanasia of affected animals. Knowledge of the disease by owners and breeders, as well as the genotyping of their animals, may prevent the spread of the variant among lineages and also assist veterinarians in differential diagnosis and management of cases of canine degenerative myelopathy. The genetics of Brazilian Golden Retriever were mainly derived from USA bloodlines. With this in mind, we may speculate that the results observed in this study may be influenced by the lower prevalence of the SOD1:c.118G>A variant previously found in American Golden Retrievers. The results obtained in the present study, combined with previous studies that described the occurrence of this variant as rare in Golden Retrievers, lead us to speculate that this variant does not impact the Brazilian Golden Retriever dogs. Keywords: dogs, canine degenerative myelopathy (CDM), neurodegenerative disease, genotyping, SOD1, variants.